The Weight of Living Autonomy, Care, and Responsibility for the Self - McKearney, Patrick (2018)
What control should we have over our death? In this paper, I re-examine the way this question has been approached in the euthanasia debate by exploring what it means to take responsibility for one's own life, especially in the face of mental disability. I do so through presenting anthropological research on the role of care, autonomy, and responsibility in L'Arche-a Christian organization in the United Kingdom in which people with and without learning disabilities share community- to identify, contextualize, and challenge central assumptions about agency in the euthanasia debate.
Keywords: Learning disability; Agency; Autonomy; Care; Euthanasia; Responsibility; Social Anthropology